Step-by-step guide for electrochemical generation of highly oxidizing reactive species on BDD for beginners - Castillo-Cabrera, G. Xavier; Pliego-Cerdán, Caroline I.; Méndez, Erika; Espinoza-Montero, Patricio J. (Frontiers in Chemistry, 2024)
Selecting the ideal anodic potential conditions and corresponding limiting current density to generate reactive oxygen species (ROS), especially the hydroxyl radical ( • OH), becomes a major challenge when venturing into advanced electrochemical oxidation processes. In this work, aA step-by-step guide forto the electrochemical generation of • OH on boron-doped diamond (BDD) for beginners is shown, in which the following steps are discussed: i) BDD activation (assuming it's new), ii) electrochemical response of BDD (in electrolyte and in Ferri/Ferro-cyanide), iii) Tafel plots using sampled current voltammetry to evaluate the overpotential region where • OH are mainly generated, iv) a study of radical entrapment in the overpotential region where • OH generation is predominant according to the Tafel plots, v) finally, the previously found ideal conditions are applied in the electrochemical degradation of amoxicillin, and the instantaneous current efficiency and relative cost of the process are reported.ICE and cost. 1 Con formato: Color de fuente: Rojo Con formato: Color de fuente: Rojo Código de campo cambiado 2 This is a provisional file, not the final typeset article 2005; Yang et al. , 2019). As electrode, BDD is very versatile material, as it has unique electronic properties. It is a non-active electrode, i.e., its chemical structure is not compromised by the redox processes to which it may be subjected, although its reticular terminations are susceptible to slight changes during oxidation and reduction (Berenguer et al., 2019). As it has a very wide potential, this electrode has been used for multiple applications in electroanalytical chemistry (M.